The use of traditional and complementary medicine to conceive, during pregnancy and the postpartum period in Kuala Muda district, Kedah, Malaysia / Roksanah Shaukat Ali - Shaukat Ali, Roksanah (2018)
Traditional and complementary medicine (T&CM) has grown its roots in the Malaysian healthcare system. Though T&CM is established worldwide, the regulations on its practices are varied with limited reliable information sources. This thesis aims to determine the use of T&CM among women trying to conceive, during pregnancy and the postpartum period by exploring the prevalence, pattern and disclosure of T&CM use. In-depth qualitative interviews were carried out among three major Malaysian ethnic groups, i.e. Malays, Chinese and Indians, until the saturation point for this study was achieved. Concurrently, quantitative surveys were done on 374 participants by using self-administered questionnaires. Qualitative data were analysed thematically while quantitative data were represented via descriptive statistics. Evidence presented show that the prevalence of T&CM use is high, which has been identified in the quantitative study (n=285, 76.2%). A majority of the participants used T&CM during the postpartum period (n=237, 83.2%) and the most popular reason for use was to aid postpartum recovery (n=226, 79.3%). Although the most frequent T&CM modality used was traditional Malay massage (n=170, 59.6%), biological based therapies (n=272, 95.4%) was the highest among all five categories of T&CM. Non-users rejected T&CM mainly due to concerns of potential risks and adverse effects of T&CM (n=42, 47.2%). T&CM disclosure rate was 42.8% (n=122). The lack of concern by healthcare providers on T&CM use, the perception that T&CM will not disrupt conventional medicines and the assumption that T&CM is safe were the most popular reasons for non-disclosure of T&CM use. In conclusion, although the benefits and safety of using T&CM have not been well documented, this study reveals that women are practising T&CM to conceive, during pregnancy, and the postpartum period. The demand for T&CM has opened the floodgates for commercial traditional products into the Malaysian market, so much so that it has become out of control. Hence, healthcare professionals should realise their roles in aiding the integration of T&CM as part of the mainstream healthcare system in order to optimise patient care and prevent harm.